A distributed cogeneration system with a two-stage solar-driven biomass gasifier for heating, power and hydrogen in Northern China. (October 2018) - Wu, Haifeng; Liu, Qibin; Bai, Zhang; Xie, Gengxin; Zheng, Jie
Abstract: In this work, a cogeneration system with a two-stage solar-driven biomass gasifier is proposed to achieve the multiple outputs, i.e., generating power and heating during the heating period and producing hydrogen during the non-heating period in Northern China. The thermodynamic performances of the system under the design and off-design conditions are investigated. The solar-biomass gasification is divided into two stages, i.e., pyrolysis and gasification in sequence. The mid-temperature solar energy (around 673 K) from parabolic trough collectors is utilized to drive biomass pyrolysis, and the high-temperature solar energy (around 1150 K) from heliostats with point-focus solar collection technology is used to drive the gasification. In the heating period, the gasified syngas as a solar fuel is directly fed into a gas turbine for generating electricity, then a heat recovery steam generator (HRSG) is deployed to produce steams for heating. An energy storage module (i.e. gas tank) is introduced to offset heating at night. The primary energy efficiency of the system is 56.1%, while the rate of stored energy to the syngas based chemical energy is up to 35.66%. The energy storage module weakens the influence of time-varying solar irradiations on system performances, and the steady and efficient utilization of solar energy are achieved. In the non-heating period, the gasified syngas can be converted into hydrogen with the water-gas shift reaction. The above results indicate that the proposed system provides a promising complementary utilization approach of multiple energies (solar energy and biomass) in Northern China.